2015
DOI: 10.1038/srep16365
|View full text |Cite
|
Sign up to set email alerts
|

Inversion of Supramolecular Chirality by Sonication-Induced Organogelation

Abstract: Natural helical structures have inspired the formation of well-ordered peptide-based chiral nanostructures in vitro. These structures have drawn much attention owing to their diverse applications in the area of asymmetric catalysts, chiral photonic materials, and nanoplasmonics. The self-assembly of two enantiomeric fluorinated aromatic dipeptides into ordered chiral fibrillar nanostructures upon sonication is described. These fibrils form organogels. Our results clearly indicate that fluorine-fluorine interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 64 publications
0
27
0
Order By: Relevance
“…However, in few solvents (aromatic solvent and long-chain aliphatic alcohol) viscous precipitation were observed. Later, we noticed that sonication 27,30,[32][33][34][35] is an interesting stimulus to induce gelation in this system.…”
Section: Resultsmentioning
confidence: 95%
“…However, in few solvents (aromatic solvent and long-chain aliphatic alcohol) viscous precipitation were observed. Later, we noticed that sonication 27,30,[32][33][34][35] is an interesting stimulus to induce gelation in this system.…”
Section: Resultsmentioning
confidence: 95%
“…Beyond the intramolecular and intermolecular factors, there are also various external stimuli that can modulate supramolecular chirality, such as heat, pH, light, sonication, and solvents, and provide abundant references for dynamic tuning . Feringa et al.…”
Section: Dynamic Modulation By External Stimulimentioning
confidence: 99%
“…Beyondt he intramolecular and intermolecular factors, there are also various external stimuli that can modulate supramolecular chirality,s uch as heat, [30] pH, [31] light, [32] sonication, [33] and solvents, [34] and provide abundant references for dynamic tuning. [35] Feringa et al reported reversible chirality control by using UV and visible light in as elf-assembling molecular system based on ad ithienylethene photochromic unit functionalized with (R)-1-phenylethylamine-derived amides, in which molecular and supramolecular chirality could communicate.…”
Section: Dynamic Modulation By External Stimulimentioning
confidence: 99%
“…Molecular structures of frequency responsive systems. References[58][59][60][61][62][63][64][65][66].…”
mentioning
confidence: 99%